Impact of Pore-Scale Characteristics on Immiscible Fluid Displacement. (15th May 2020) - Mahabadi, Nariman; van Paassen, Leon; Battiato, Ilenia; Yun, Tae Sup; Choo, Hyunwook; Jang, Jaewon
Abstract : Immiscible fluid flows (drainage displacement) where nonwetting fluid invades porous media filled with wetting fluid are frequently observed. Numerous studies have confirmed the existence of three different displacement patterns which depend on the viscosity ratio and capillary number: stable displacement, viscous fingering, and capillary fingering. However, the phase boundary and displacement efficiency of each displacement pattern can vary significantly depending on the characteristics of the experimental and numerical tools employed. In this study, a three-dimensional (3D) tube network model was extracted from 3D X-ray computed tomography images of natural sand. The extracted network model was used to quantitatively outline the phase boundary of the displacement pattern and to examine the displacement efficiency for wide ranges of viscosity ratios and capillary numbers. Moreover, the effects of the tube size distribution and tube connectivity on the displacement characteristics were investigated. A transition regime between the viscous fingering and capillary fingering zones with regard to the displacement efficiency was observed for the first time. As the tube size distribution became uniform, the viscosity effect increased. As the tube connectivity decreased to 4.6, the phase boundary became similar to that of a two-dimensional network. The characteristic changes of the phase boundary and displacement efficiency were highlighted through local gradient diagrams.